Cyclodextrin-metal-organic framework (CD-MOF)/ organic-inorganic hybrid composite as a potential material for drug delivery devices - Abuçafy, Marina Paiva [UNESP]; Mori, Aline Sayuri [UNESP]; Caetano, Bruno Leonardo [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Chiavacci, Leila Aparecida [UNESP] (Elsevier, 2024)
Metal-organic frameworks (MOFs) constitute a distinctive class of materials composed of metal ions or clusters intricately linked by organic ligands. Among MOFs, γ-cyclodextrin- based MOFs (γ-CD-MOFs) have attracted significant attention for their potential in edible, non toxic, and renewable applications. This study introduces a facile and environmentally friendly method for synthesizing γ-CD-MOFs, integrated with a ureasyl-polyether film to develop a cutaneous patch exhibiting a unique release profile. This system's physicochemical properties, encapsulation, and release kinetics were rigorously evaluated using Ibuprofen as a model anti-inflammatory drug. The resulting films, integrated with γ-CD-MOFs, exhibited an impressive encapsulation efficiency exceeding 80 %, and a controlled release effect. Notably, the system demonstrated superior ability in sustaining Ibuprofen release, indicating a synergistic combination of multiple mechanisms, including drug diffusion and erosion of metal-organic frameworks. The comprehensive findings underscore the potential of these systems as effective topical drug-delivery platforms, meeting the stringent criteria of releasing less than 10 % of the payload within 12 h. This study emphasizes the crucial role of rational MOF and organic-inorganic hybrid selection, shedding light on the intricate interplay of chemical parameters among MOF, polymer, and drug, which significantly influence drug adsorption and release dynamics. The outcomes presented herein contribute to advancing our understanding of MOF-based drug delivery systems and highlight their promising future applications in pharmaceutical research.
Keywords: Anti-inflammatory; Cyclodextrin, hybrid membrane; Drug delivery; Metal-organic framework